Theravada Buddhism and Thai Luxury Fashion Consumption - McAleer, Michael (Journal of Reviews on Global Economics, 2016)
This paper reviews the Thai national character according to Hofstede's (1991, 2001, 2017) cultural dimension theory and Komin's (1991) nine values cluster (Psychology of the Thai people), analyses the social hierarchy of Thai consumers according to the Luxury 4P Taxonomy (Han et al., 2010), integrates the Theory of Cultural Capital (Bourdieu, 1984, 1986), and expounds the features of social class. The global luxury fashion industry has grown significantly in recent years, but much of the research has been limited to conspicuous consumption and social identity. This paper involves religious beliefs that are argued to influence luxury purchasing motives. The purpose of the paper is to develop an analytical framework to aid in understanding luxury fashion consumption in a Buddhist country such as Thailand in order to inform luxury products vendors on how to improve their marketing strategies.